HF-free dry gel synthesis of MIL-100(Fe) for adsorptive removal of salicylic acid in wastewater treatmenture - Wan Ishak, Wan Nuraishah; Mohd Sabri, Nurul Syafiqah; Ying, Pei Lim; Huey, Ling Tan (Universiti Teknologi MARA Shah Alam, 2025)
This study reports an HF-free dry-gel conversion route to synthesise MIL-100(Fe) and evaluate its performance for adsorptive removal of salicylic acid from wastewater. Comprehensive characterisation of the material was conducted using XRD, FT-IR, FESEM and zeta potential. The dry gel conversion method successfully produced MIL-100(Fe) with an amorphous structure with an average particle size of 27 μm. Adsorption experiments achieved a maximum salicylic acid removal efficiency of 82.62% across the tested range (10 to 50 µg/mL), corresponding to an adsorption capacity of 80.93 mg/g at 120 minutes. Significant reductions in FT-IR peaks associated with carboxylic acid O–H stretching vibrations were observed, particularly in regions 3600 to 4000 cm−1 and 2500 to 3600 cm−1 . These changes indicate strong interactions between the carboxyl groups of salicylic acid and the active sites on the MIL-100(Fe) surface, confirming effective adsorption and removal of salicylic acid. These findings demonstrate that MIL-100(Fe) synthesised through a hydrofluoric acid-free dry gel conversion route is an effective and environmentally benign adsorbent for the removal of pharmaceutical pollutants from wastewater.